Rohingya Crisis In Bangladesh: Causes, Consequences And Remedies - Islam, Md. Ashraful (Al-Makki Publisher, 2023)
Bangladesh, a nation marked by its dense population, continues to wrestle with multifaceted challenges even 52 years after gaining independence while navigating the sophistications of development. Among these challenges, the pressing issue of the Rohingya people's plight takes center stage, with various forms of oppression, including mass killings, executions, forced labor, deportation, and the denial of fundamental human rights, rendering them stateless. This study seeks to dissect the roots of the Rohingya crisis and explore its repercussions on Bangladesh. Employing an exploratory research approach, data from secondary sources were qualitatively analyzed using content analysis to discern underlying themes and patterns. The findings reveal that the Rohingya crisis is primarily driven by the lack of documentation, the rise of authoritarianism, and a complex religious landscape. Additionally, the paper identifies social, economic, and environmental challenges as direct consequences of refugee migration in Bangladesh. These insights hold significant implications for policymakers and practitioners actively involved in addressing the Rohingya crisis. Offering a comprehensive analysis, the study also proposes practical policy recommendations grounded in the specific context of the crisis, aiming for tangible applications in real-world scenarios.